The application of coal mining waste to the production of construction ceramics: radiological and mechanical aspects - M. Bonczyk; J. Rubin (Materiales de Construccion, 2022)
The article presents the results of research on the physical and radiological properties of building ceramics made of mining waste. One method of using mining waste is to use it as aggregate in road construction. However, this alone is not enough to dispose of the entire amount of waste generated. Another promising method of using mining waste is the production of building ceramics (bricks). However, some properties (e.g. the content of natural radionuclides) of the waste may limit the possibility of such use. In the scope of this work, the properties of bricks made from mining waste - shale collected from dumps, were examined. It has been shown that the properties of bricks prepared in this way meet the criteria set out in various standards and legal acts and can be used in construction.